Sustainable Competitiveness Through Quality Transformation: A Longitudinal Analysis Of Quality Award Winners And A Proposed Framework - Idris, Mohd Ashari; Mohamed Zairi, Mohamed Zairi (Asian Academy of Management (AAM), 2002)
Quality management is a dynamic philosophy that underlines the organisational adaptation and proactive transformation that enables firms to reap real benefits from market opportunities. The faster the market changes, the quicker the transformation that is required for sustaining the firm's internal capabilities and its external competitiveness. Under a competitive pressure, a firm will need to learn faster and lead in best practice for operational excellence and continuously finding ways to shield its advantage from imitation. In the search for determinants for sustainability, this article analyses best practices adopted by quality award-winning organisations and synthesises a collection of critical factors that could assist organisations in improving their performance. From a longitudinal learning on how these leading organisations led themselves into a new sustaining paradigm, the article makes explicit the factors that were considered of paramount importance to sustainability. These success factors become a basis for others to leapfrog ahead into a new performance orbit. A proposed model for sustaining competitiveness has been developed from the creative learning of best practices of leading organisations. This proposed framework presents companies with an opportunity to emulate successful implementation of TQ-based initiatives, and to embed these pioneering concepts, particularly in the context of emerging countries.